Analisis Tentang Tindakan Penagihan Yang Melawan Hukum Terkait Pinjaman Online dari Fintech Ilegal (Studi Kasus Atas Putusan Nomor 438/Pid.Sus/2020/PN.Jkt.Utr) - Alfin Rafael; Sugandi Ishak (Jurnal Hukum Adigama, 2021)
In Indonesia, there are 3,107 illegal fintech companies. The author focuses on illegal collection actions related to online loans from illegal fintech as stated in Decision Number 438/Pid.Sus/2020/PN.Jkt.Utara. When collecting an online loan from the victim, the defendant used harsh words towards the victim by sending a voice note via Whatsapp with words such as "bad dog", "devil's child", an insult to the victim. The problems that the author raises are How Peer To Peer Lending (P2P Lending) Debt Collection Actions in the Perspective of Criminal Law and How to find out whether the fintech is registered or not and what the sanctions are in terms of the Law of the Republic of Indonesia Number 19 of 2016 concerning Amendments to the Law Number 11 of 2008 concerning Information and Electronic Transactions. The author in his analysis stated that the act of billing using harsh words carried out by the defendant violated Article 310 of the Criminal Code and the illegal company could be subject to criminal sanctions based on Article 32 of Law no. 3 of 1982 concerning Compulsory Company Registration. The author concludes that the act of billing using harsh words committed by the defendant violated Article 310 of the Criminal Code and must be accompanied by a complaint to the police and related to the illegal company can be subject to sanctions by Article 32 of Law no. 3 of 1982 concerning Compulsory Company Registration.